Effectiveness of Discourse Markers Usage in Improving High School Students’ Essay Writing performance - Sanusi, Kamaldeen Kola (NIU Journal of Humanities, 2018)
The present study sought to examine the effectiveness of discourse markers usage in improving high school students’ essay writing performance with respect to two dimensions of appropriateness of usage and usage frequency. The study employed two group quasi-experimental research design. All 160 students participants were randomly divided into either experimental or control group. A pre-test was administered to gain the necessary background of student participants' knowledge of the subject-matter in essay writing before treatment. To measure the two groups' performances on their written output, after sessions of explicit instruction for experimental group on the established areas, a post-test was also conducted. Using a range of measures, the obtained findings revealed a low positive relationship in the pretest essay writing performances between students in control and experimental. There was no significant difference in the pre-test scores between students in the two groups as they all lack skill of appropriate usage of discourse markers. Statistically significant differences were thereafter recorded between pre-test and post-test scores in the writing performance of the students in Experimental group as a result of the treatment. The conclusion suggests that students’ writing abilities are improved not only on contribution of length and lexico-grammatical intricacy, but also through consideration of appropriateness in the usage of the discourse markers and how much and how frequently they make use of these transition elements can significantly predict effective essays’ writing quality. Keywords: Discourse markers, Appropriate usage, Frequency, Essay writing.